A study of local adaptation in the Iberian honeybee (Apis mellifera iberiensis) using a reciprocal translocation experiment - Lopes, Ana (2018)
In Europe, several translocation experiments suggested that native populations of Apis mellifera are adapted to local climate and flora. However, so far, no study has been conducted on the Iberian honeybee, Apis mellifera iberiensis. The goal of this study was to assess the existence of genotype-environment interaction (GEI), and consequently local adaptation, in the Iberian honeybee. In 2015 two apiaries were set up, each one with 36 colonies (18 of the origin Bragança and 18 of the origin Vila do Bispo), in two latitudinal extremes of Portugal: Bragança (north) and Vila do Bispo (south). Several traits of the 36 colonies were measured for almost 2 years, including: number of brood and pollen cells, honey yield, survival, and Varroa destructor infestation. The analyses were performed using t-Student and Mann-Whitney tests to compare those traits between the two origins in the same apiary and the same origin between the two apiaries. The survival analysis was performed using the Cox proportional hazard model in R. Colonies of the southern origin Vila do Bispo showed a tendency to collect more pollen and consequently they produced a higher number of brood cells, had a higher varroa infestation level and a lower survival rate than colonies of the origin Bragança in both locations. Honey yield was the only trait that showed existence of GEI, and therefore local adaptation, since the local honeybees had a higher honey production in their apiary of origin. Additionally, the differences between the two origins were sharper in more favourable environments where the honeybees can better express their genetic potential. Our findings highlight the importance of protecting local honeybee diversity in a period of increasing selection pressures such as climate change, agricultural land overuse and novel pathogens and parasites.